Estimologi irfani - Sari, Sinta Permata (Maliki Interdisciplinary Journal, 2025)
Irfani epistemology is an approach in Islamic philosophy that emphasizes the importance of intuitive experience, spiritual illumination, and inner knowledge in understanding reality. In contrast to rational and empirical epistemology which relies on logic or sensory experience, Irfani’s epistemology is based on direct experience through purification of the soul and a deep relationship with God. In this tradition, knowledge is not simply considered the result of a discursive process, but as a gift given to the pure heart. This approach involves aspects of ethics, spirituality and contemplation, so it has significant implications for outlook on life and religious practice. This article examines the basics of Irfani’s epistemology, methods of obtaining it, and its relevance in the modern context. By integrating intellectual and spiritual dimensions, Irfani’s epistemology offers an alternative paradigm in understanding the nature of truth and reality